The Ḥadīth of the Seven Earth Layers: A Scientific and Validity-Based Reappraisal - Muhammad Anshori; Abdul Haris (Millati: Journal of Islamic Studies and Humanities, 2025)
This study examines the hadith concerning the seven layers of the earth through a scientific lens. Its primary objective is to rigorously evaluate the hadith’s validity, encompassing both its chain of transmission (sanad) and textual content (matn). Employing a descriptive-analytical methodology with a critical hadith approach, this research addresses a salient aspect of contemporary hadith scholarship: the verification of prophetic traditions through modern scientific discoveries. The analysis assesses the reliability of the sanad, scrutinizes the matn, and investigates its congruence with current scientific knowledge. Findings indicate that the hadith attains a high degree of authenticity based on narrator verification and textual analysis. Scientifically, the concept of seven terrestrial layers referenced in the hadith demonstrates significant alignment with geological stratification models, ranging from the crust to the inner core. Consequently, this tradition is not only authenticated within the framework of hadith sciences but also proves consistent with modern scientific understanding, revealing embedded scientific insights empirically verified in the contemporary era.